The Relationship between Parents' Knowledge about the Growth Period of Children's Teeth with the Occurrence of Persistence - keumala, cut ratna; Mardelita, Sisca; Ridara, Rina (Journal Dental Health, 2023)
Persistence is a deciduous tooth that has not yet fallen out in time so that the fixed tooth begins to erupt, then the fixed tooth will look for the direction of the decidui tooth that has been removed, if the decidui tooth is not removed it will cause the tooth to cram and malocclusions in the replacement tooth, in the growth of the child's teeth requires the attention and knowledge of parents about the growth period of the child's teeth. The purpose of this study was to determine the relationship between parents' knowledge about the growth period of children's teeth with the occurrence of persistence in grade I and II students at SDN 71 Mibo, Banda Aceh City. This research method is analytical with a cross-sectional design. The sampling technique is the Total Population, which is 36 students and their parents. This research was conducted from 02 to 09 February 2022. The results of the study with the chi-square statistical test, namely there is a significant relationship between maternal knowledge about the growth period of children's teeth and the occurrence of persistence in grade I and II students at SDN 71 Mibo Banda Aceh City with p-value = 0.006 (p<0.05). It can be concluded that there is a relationship between parents' knowledge about the growth period of children's teeth and the occurrence of persistence in grade I and II students at SDN 71 Mibo, Banda Aceh City. It is recommended to parents increase their knowledge about dental persistence through counselling carried out by health workers and so on, to parents of students whose children experience persistence so that tooth extraction is immediately carried out.